Seventeen new species of the spider genus Teutamus Thorell, 1890 from Southeast Asia (Araneae: Liocranidae) - Dankittipakul P. (2014)
Seventeen new species of the spider genus Teutamus Thorell, 1890 are described from Southeast Asia: two species from southern Thailand and Malaysia (T. rama sp. nov. and T. brachiatus sp. nov.); seven species from the Malay Peninsula (T. serrulatus sp. nov., T. apiculatus sp. nov., T. lioneli sp. nov., T. calceolatus sp. nov., T. globularis sp. nov., T. leptothecus sp. nov. and T. deelemanae sp. nov.); five species from Sumatra, Indonesia (T. orthogonus sp. nov., T. tortuosus sp. nov., T. rollardae sp. nov., T. poggii sp. nov. and T. sumatranus sp. nov.); one species from Borneo, Indonesia (T. spiralis sp. nov.); one species from Indonesia and Malaysia (T. seculatus sp. nov.); and one species from the Philippines (T. hirtellus sp. nov.). The type species, T. politus Thorell, 1890, was examined and illustrated. This speciose genus of generalized ant mimics is common throughout the forests of the Sundaland sub-region of Southeast Asia. © 2012 Copyright Taylor and Francis Group, LLC.